Characterizing Explosives and Blasting Emissions (International Society of Explosives Engineers) - MacDonald B. Johnson; Douglass P. Bacon (International Society of Explosives Engineers, 1995)
"W ith the advance of science, rise of public interest in environmental matters, and continuing erosion of air quality, federal and state regulators are demanding an increasing complex array of data concerning emissions produced by burning and detonating energetic materials. The U.S. Department of Defense, one of the world’s largest consumers of energetic materials, now must characterize combustion products resulting from open burning/open detonation disposal operations. The catch-all phrase “below detection limits” no longer satisfies the regulators who nowwant testing to delve into the ppt level for volatile organic compounds and ppt level for semivolatile organic compounds."